2022
DOI: 10.1002/cbdv.202200401
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside in the Treatment of NAFLD/NASH

Abstract: Non‐alcoholic fatty liver disease (NAFLD) is the commonest reason for chronic liver diseases in the world and is commonly related to the hepatic manifestation of the metabolic syndrome. Non‐alcoholic steatohepatitis (NASH) is a deteriorating form of NAFLD, which can eventually develop into fibrosis, cirrhosis, and liver cancer. The reason for NAFLD/NASH development is complicated, such as liver lipid metabolism, oxidative stress, inflammatory response, apoptosis and autophagy, liver fibrosis and gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 164 publications
0
4
0
Order By: Relevance
“…Finally, they discovered that it played an essential role in the recruitment of Th1 cells to kidney and mediating the renal ischemia-reperfusion injury [ 94 ]. Currently, researchers identified again that infiltrating immune cells can influence the process of AKI by the signaling pathways of CXC chemokines (such as CXCL1/CXCR2 axis) and so on [ 95 ]. In addition, Medeiros et al analyzed COVID-19 patients evolving with AKI.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…Finally, they discovered that it played an essential role in the recruitment of Th1 cells to kidney and mediating the renal ischemia-reperfusion injury [ 94 ]. Currently, researchers identified again that infiltrating immune cells can influence the process of AKI by the signaling pathways of CXC chemokines (such as CXCL1/CXCR2 axis) and so on [ 95 ]. In addition, Medeiros et al analyzed COVID-19 patients evolving with AKI.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…Previous studies have found that SAL can attenuate CCL4-induced liver injury by inhibiting ROS deposition and restoring mitochondrial structure and function ( Lin et al, 2019 ). SAL also inhibits the activity of NLRP3 inflammasome and reduces the release of inflammatory factors, thereby alleviating hepatic inflammatory injury ( Qu et al, 2022 ). In addition previous studies have found that SAL inhibits L-glu-induced activation of JNK and MAKP, thereby inhibiting cytotoxicity and protecting brain tissue from toxic substances ( Lee et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sorbiferin (SDS) in Rhodiola rosea L. ( Hu et al, 2021 ), improves abnormal lipid metabolism, regulates the composition of gut microbiota ( Qu et al, 2022 ), effectively reverses FXR deficiency during NASH. SDS was intragastrically administered at a dose of 20 mg/kg/day for 4 weeks.…”
Section: Role Of Natural Products and Their Extracts In Fatty Liver D...mentioning
confidence: 99%